Analysis of genes coding for CD46, CD55, and C4b‐binding protein in patients with idiopathic, recurrent, spontaneous pregnancy loss. Issue 6 (23rd April 2013) - Mohlin, Frida C.; Mercier, Eric; Fremeaux‐Bacchi, Veronique; Liszewski, M. Kathryn; Atkinson, John P.; Gris, Jean‐Christophe; Blom, Anna M.
<x xml:space="preserve">Abstract</x> Since a tightly regulated complement system is needed for a successful pregnancy, we hypothesized that alterations in complement inhibitors may be associated with idiopathic, recurrent miscarriage. We sequenced all exons coding for three complement inhibitors: C4b‐binding protein (C4BP), CD46, and CD55 in 384 childless women with at least two miscarriages that could not be explained by known risk factors. Several alterations were found in C4BPA, of which the R120H, I126T, and the G423T mutations affected the expression level and/or the ability of recombinant C4BP to serve as cofactor for factor I. The only variant in C4BPB was located in the C‐terminal part, and did not impair the polymerization of the molecule. Our results identify for the first time alterations in C4BP in women experiencing recurrent miscarriages. We also found four CD46 alterations in individual patients that were not found in healthy controls. One of the rare variants, P324L, showed decreased expression, whereas N213I resulted in deficient protein processing as well as an impaired cofactor activity in the degradation of both C4b and C3b. The identified alterations may result in in vivo consequences and contribute to the disorder but the degree of association must be evaluated in larger cohorts.